2016
DOI: 10.1001/jamafacial.2016.0474
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Unmet Need for Cleft Lip and/or Palate Surgery in India

Abstract: raniofacial cleft anomalies are common, affecting 1 in 600 live births annually. 1 However, cleft lip and/or palate (CL/P) disproportionately affects newborns in low-and middle-income countries (LMICs) owing to substandard nutrition and a lack of prenatal care. 2,3 Infants born with CL/P in LMICs face significant barriers to treatment, which often lead to prolonged disfigurement, social stigma, speech impairment, and feeding difficulty that may result in malnutrition and even death. [4][5][6] Although CL/P is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In reality, it is identified that 18.76% of Indian OFC are not treated. [ 20 ] From the result of this study and lancet commission report our estimate of about 79,430 people with OFC have or had no access to surgical care. This has to be addressed on a priority basis and appropriate care instituted.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In reality, it is identified that 18.76% of Indian OFC are not treated. [ 20 ] From the result of this study and lancet commission report our estimate of about 79,430 people with OFC have or had no access to surgical care. This has to be addressed on a priority basis and appropriate care instituted.…”
Section: Discussionmentioning
confidence: 90%
“…The birth prevalence of OFC for India was collected. [ 18 ] From previously published literature,[ 20 ] the unmet treatment need for mid-year 2014 derived projections and added another 5% as per the methodology to compute the 2016 projection including untreated palate and lip OFC. This estimate was used to make the unmet surgical need of the population.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the database will be used to identify, monitor, and analyze clinical outcomes and epidemiologic trends in health care utilization, access, and quality; develop evidence-based practice guidelines; and support clinical research and education. [1][2][3][4][5][6] Information acquired from the database will serve as a foundation for submitting grants to outside organizations, allowing the AAFPRS to continue sustaining FACE TO FACE initiatives.…”
mentioning
confidence: 99%
“…It is estimated that at least about 72,000 people still do not have access to surgery. [ 2 ] In spite of the best care, complications do arise after surgeries. [ 3 ]…”
mentioning
confidence: 99%